A New Color Image Compression Based on Fractal and Discrete Cosine Transform (International Journal of Engineering and Computer Science, 2014)
Fractal Image Compression is a compression method in which self similar nature of an image is used. It is a way to encode images that require less storage space. In this paper, an implementation based on fractal with quadtree and Discrete Cosine Transform is proposed to compress the color image. Initially the image is segmented and DCT is applied to each block of the image. Then the block values are scanned in zigzag manner to prevent zero coefficients. The resultant image is partitioned as fractals by quadtree technique. Finally the image is compressed using Run Length encoding Technique. Experimental results show that the proposed technique compresses the image effectively with high PSNR value and SSIM index.